Overexpressing the H‐protein of the glycine cleavage system increases biomass yield in glasshouse and field‐grown transgenic tobacco plants. Issue 1 (22nd July 2018) - López‐Calcagno, Patricia E.; Fisk, Stuart; Brown, Kenny L.; Bull, Simon E.; South, Paul F.; Raines, Christine A.
Summary: Photorespiration is essential for C3 plants, enabling oxygenic photosynthesis through the scavenging of 2‐phosphoglycolate. Previous studies have demonstrated that overexpression of the L‐ and H‐proteins of the photorespiratory glycine cleavage system results in an increase in photosynthesis and growth in Arabidopsis thaliana . Here, we present evidence that under controlled environment conditions an increase in biomass is evident in tobacco plants overexpressing the H‐protein. Importantly, the work in this paper provides a clear demonstration of the potential of this manipulation in tobacco grown in field conditions, in two separate seasons. We also demonstrate the importance of targeted overexpression of the H‐protein using the leaf‐specific promoter ST‐LS1. Although increases in the H‐protein driven by this promoter have a positive impact on biomass, higher levels of overexpression of this protein driven by the constitutive CaMV 35S promoter result in a reduction in the growth of the plants. Furthermore in these constitutive overexpressor plants, carbon allocation between soluble carbohydrates and starch is altered, as is the protein lipoylation of the enzymes pyruvate dehydrogenase and alpha‐ketoglutarate complexes. Our data provide a clear demonstration of the positive effects of overexpression of the H‐protein to improve yield under field conditions.